PROFESSIONALIZATION THROUGH COLLABORATION IN TEACHER EDUCATION – IDENTIFYING THE STATUS QUO - Bush, Annika; Grotjohann, Norbert (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Teacher collaboration together with (self-)reflection is a key factor to improve teacher professionalism. Nevertheless, collaboration among teachers is not being used sufficiently. One approach to change this is to implement collaborative behaviours earlier, in the university-based teacher-training. To develop eligible methods, the status quo must be defined first. Therefore, this paper researches how, with whom and why education students and trainee teachers collaborate. The study is based on a mixed methods design: At first, qualitative interviews were held to define the structures of collaboration. Main results were, that especially students in the examined internship prefer to collaborate with teachers rather than with their fellow students. Also, collaboration happens spontaneously, and planned structures between teachers and interns are rarely found. All in all, the main collaboration form is exchange (of materials and information) whereas higher forms of collaboration are seldomly realized. To gain more profound numbers, the results were transformed into a standardized questionnaire. In this second quantitative study, 1763 educational science students and trainee teachers participated. The statistic results will be the base for a third study which will be qualitative again in form of episodic interviews. The aim is to explain the quantitative results and point out structures, where universities and schools can start to act and improve the teacher collaboration at an early point of their career to improve teacher professionalization through teacher education. This paper presents the results of the first two studies as well as the leading questions for the future interviews.